Nutrient inputs shape ecosystem functioning gradients along the pristine, upper Neretva River, Bosnia and Herzegovina - Rubén Del Campo; Barbara Jechsmayr; Veronika Settles; Melanie Ströder; Gabriel Singer (Natura Sloveniae)
Ecosystem functions are the backbone of ecosystem services that rivers provide to human societies. Ecosystem functioning emerges from the interaction between biological communities and their environment. As environmental conditions in rivers change along their longitudinal continuum, so does functioning. Sometimes, these changes do not follow smooth gradients but rather great discontinuities. This can be the case in calcareous, karstic rivers due to the sudden massive inputs of groundwater along the landscape, a typical phenomenon for Balkan rivers. Despite their high geodiversity and their great ecological value, Balkan rivers remain understudied. Here, we investigated how ecosystem functions and their diversity (estimated as multifunctionality) change along the continuum of the karstic, free-flowing Neretva River in Bosnia and Herzegovina. For this purpose, we measured a subset of fundamental ecosystem functions (ecosystem gross primary production, biofilm net primary production and enzymatic activities, organic matter decomposition) in 11 river reaches from the Neretva headwaters to river sections upstream of the Jablanica reservoir. We found different functions reached their maximum in different sections of the Neretva depending on nutrient inputs. While organic matter decomposition was highest in headwaters due to the input of nutrients from riparian vegetation, biofilm enzymatic activity expressed highest values at middle sections due to groundwater inputs of NH4+-N. Primary production was highest at the most downstream sections due to the accumulation of NO3--N and PO43--P within the catchment area. As a result, average multifunctionality peaked at sites with the highest nutrient concentration across the Neretva river continuum, indicating a stronger influence of nutrient inputs than network position. The pristine conditions of the Neretva result in oligotrophic conditions along its upper course. Our results emphasize the great sensitivity of ecosystem functioning in the Neretva to nutrient inputs and environmental discontinuities, either natural or human-made. Potential major, long-term impacts in the area might alter existing environmental gradients and thus ecosystem functioning in rivers at local and regional scale.